PELATIHAN PENGAJARAN BAHASA DENGAN MENGGUNAKAN TEKNIK TOTAL PHYSICAL RESPONSE DAN MIND MAPPING PADA GURU-GURU SEKOLAH DASAR KECAMATAN KEDUNGKANDANG MALANG - Dwi Fita Heriyawati; Junaidi Mistar; Eko Suhartoyo (LP2M Universitas Hasanuddin, 2023)
This community service applies Total Physical Response (TPR) and mind mapping to learning English. This community service activity aims to improve elementary school teachers' skills in the Kedungkandang sub-district by providing training and mentoring in TPR and mind-mapping strategies. Teachers who participate in community service activities receive innovative teaching techniques so that they can apply them in the classroom. So that the classroom atmosphere will be more enjoyable, not only by teaching traditionally by giving notes to students but also by making students participate actively in learning. For example, students do not just sit and take notes; they use gestures. Students will think and act faster in education because the material taught by the teacher will be made by mapping, known as the